Trend Produksi dan Ekspor Minyak Sawit (CPO) Indonesia - Andi Alatas (AGRARIS: Journal of Agribusiness and Rural Development Research, 2015)
This study aims to determine the trend of palm oil production, the trend of the value of production, trends of CPO(crude palm oil) export volume, trend value of Indonesian exports, as well as to determine the factors that influence the Indonesian CPO exports and to know the benefits of Indonesia's CPO. The data that used are annual data which were analyzed using regression analysis to estimate the influential factors, the analysis of RCA (Revealed Comparative Abvantage) and AR (Acceleration Ratio) were used to determine the comparative advantage of the Indonesian palm oil in international market.The results showed that the trend of Indonesian palm oil production on average was increased, while the trend of the value of production, the export volume trend, and the trend of Indonesian CPO export value also increased from year to year. The high productivity of Indonesian palm oil production allows the State Indonesia's CPO to exports to neighboring countries, such as China, India, and the Netherlands. From the results of research on the factors that influence the CPO exports to China state that the International CPO price, exchange rate, per capita income, population, and the price substitution (soybean). Factors affecting the CPO exports to China were the CPO price International, capita income of, population, and the price substitution. Factors that affecting CPO exports to Netherland countries were the domestic price, capita income, population, trend, and subtitusi price.Analysis to determine the comparative advantage to Indonesian CPO market showed that Indonesian CPORCA value was higher than the value of the RCACPO World wide  average, while the World RCA value of 1,06, this showed that the market share of Indonesian CPO superior and capableto compete in international market. The growth of Indonesian CPO export has accelerated and higher than other countries in the World (AR =1,009).